Evolution of conditional and unconditional commitment. (7th May 2020) - Quillien, Tadeg
Highlights: Outside options make social relationships unstable. Altruism can evolve as a costly signal of commitment to a relationship. Natural selection favors commitment signals whose meaning is unambiguous. Abstract: We show that altruism can evolve as a signaling device designed to solve commitment problems in interactions with outside options. In a simple evolutionary game-theoretic model, uncertainty about agents' incentives to stay in a relationship can cause the relationship to collapse, because of a vicious circle where being skeptical about one's partner's commitment makes one even more likely to leave the relationship. When agents have the possibility to send costly gifts to each other, analytical modeling and agent-based simulations show that gift-giving can evolve as a credible signal of commitment, which decreases the likelihood of relationship dissolution. Interestingly, different conventions can determine the meaning of the signal conveyed by the gift. Exactly two kinds of conventions are evolutionarily stable: according to the first convention, an agent who sends a gift signals that he intends to stay in the relationship if and only if he also receives a gift; according to the second convention, a gift signals unconditional commitment.